The Conundrum of Birth Tourism and American ‘Jackpot Babies’: Attitudes of Ghanaian Urban Dwellers - Allotey, Ada Adoley; Kandilige, Leander (African Human Mobility Review, 2021)
Some contemporary international migration literature highlights the utility of the acquisition of privileged citizenships by temporary migrants (birth tourists) and the inherent benefits that accrue to this category of migrants. However, scholars tend to rely solely on the subjective accounts of birth tourists to measure attitudes to the practice of deliberately migrating to a preferred destination country at an advanced stage of pregnancy to secure citizenship rights for one’s child. Employing concurrent triangulation design, survey and semi-structured in-depth interviews were used in collecting data from 260 urban dwellers in three metropolises in Ghana – Accra, Cape Coast and Kumasi – who are yet to give birth in the United States and 15 parents who already have a total of 25 American ‘jackpot babies’, to measure a broader spectrum of attitudes towards this phenomenon. This paper records a nuanced continuum of attitudes to the concept of American ‘jackpot babies’, ranging from favourable to neutral/indifference to objection to this phenomenon among Ghanaian urban dwellers.